Evangelical Higher Education: History, Mission, Identity, and Future - House, Gary K. (Catholic Education: A Journal of Inquiry and Practice, 2003)
Evangelical Christian colleges have has a unique role in the development of higher education in America and in producing Christian leadership for the world. These institutions have sought to educate and train leaders not only by transmitting knowledge and skills but also by attempting to instill moral character, integrity, and responsibility in their students. They have endeavored to educate according to Christian purposes, recognizing the value of integrating faith and learning. The evangelical Christian liberal arts college is especially adapted to create a context for educating the whole person. These institutions have a unique heritage, a clear purpose, a distinct identity, and a bright future.